Homeland Security: Establishment and Implementation of the United States Northern Command - Shepherd, Scott; Bowman, Steve (2005)
The Department of Defense (DoD) established U.S. Northern Command (NORTHCOM) to fight terrorism at home. Significant organizational and procedural progress has been made in setting up this organization. However, questions remain concerning interagency relationships and information sharing. This report will be updated as events dictate. CRS Report for Congress.